PHONICS METHOD AS AN ALTERNATIVE TO FULFILL THE RIGHT TO EDUCATION OF DYSLEXIC CHILDREN IN REVIEW OF LAW NUMBER 20 OF 2003 CONCERNING THE NATIONAL EDUCATION SYSTEM - Yusmulyadi, Yusmulyadi; Kurniasari, Tri Widya (PIONIR: JURNAL PENDIDIKAN, 2024)
This study is to find out how the fulfillment of the Right to Education for children with special needs who experience dyslexia through the phonics method as an alternative therapy. Many students with special needs attend public schools and they are generally dyslexic. Dyslexic children take a slower time to speak because they have difficulty remembering letters, words and sentences. This condition hampers the child's growth and development, especially in the academic process. One of the effective therapy methods in improving the reading and writing skills of dyslexic patients is phonics. This type of research is qualitative research, as a research procedure that produces descriptive data on issues related to the phonics method as an alternative therapy for dyslexic children. Judging from Law Number 20 of 2003 concerning the National Education System (UUSPN), it can be seen that the State has guaranteed legal certainty in the context of preventive protection. The research approach used is a legal and community research approach (socio legal research). The socio legal research approach is conducted to find out whether the UUSPN has accommodated the Right to Education for children with special needs who have dyslexia and whether the choice of the phonics method as an alternative therapy has become an effort to fulfill the Right to Education for dyslexic children. The phonics method can help improve the reading ability of dyslexic students, so that they can follow the learning process in class, thus the phonics method is one of the supporting factors in achieving the goals of National Education as stated in Article 3 of the UUSPN.Keywords: Phonics Method, Educational Rights, Dyslexic Children